Secure Communications for Resource-Constrained IoT Devices † - Taha, Abd-Elhamid M. (Sensors (Basel), 2020)
The importance of securing communications on the Internet of Things (IoT) cannot be overstated. This is especially the case in light of the increasing proliferation of IoT devices and instances, as well as the growing dependence on their usage. Meanwhile, there have recently been mounting concerns over a wide array of vulnerabilities in IoT communications. The objective of this work is to address constraints in IoT devices that are “resource-constrained”, which are devices that are limited in terms of computing, energy, communication, or range capabilities, whether in terms of nominal or temporal limitations. Specifically, we propose a framework for resource-aiding constrained devices to facilitate secure communication. Without loss of generalization, the framework’s viability is illustrated by focusing on a group of security functions that utilize message authentication codes, which is a strongly representative example of resource-intensive security functions. Aspects of the framework are further demonstrated in processing cores commonly used in commercial IoT devices.